Kajian Implementasi Program Banyuwangi Tanggap Stunting Di Pusat Kesehatan Masyarakat Desa Wonosobo Kecamatan Srono - Desy Dwi Anjarwati; Hary Priyanto; Niko Pahlevi Hentika (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Implementation of the Banyuwangi Response Stunting Program in Srono District, because the prevalence reached 6.98% and placed it as the 3rd highest rank in Banyuwangi Regency. The highest supplier is Wonosobo Village. The high stunting rate is because many people and including stakeholders think stunting is only about heredity, so it's considered normal. Objective: To describe, analyze, and interpret the implementation of the Banyuwangi Respond Stunting program to the people of Wonosobo Village. Method: Using qualitative principles according to constructive and participatory models. Primary data from interview results, and secondary data from the results of literature studies and various regulations relevant to the substance of the research. Result: It is difficult to reduce stunting due to ineffective prevention programs, not optimal coordination related to planning, budgeting, implementation, monitoring and evaluation, ineffective and efficient allocation and utilization of resources and sources of funds, as well as minimal assistance and outreach regarding the prevention and treatment of stunting. Conclusion: Giving all the rights of people who are vulnerable to stunting as referred to in the Banyuwangi Respond Stunting program is very important.